2014
DOI: 10.1038/ejhg.2014.183
|View full text |Cite
|
Sign up to set email alerts
|

The dystrophin gene and cognitive function in the general population

Abstract: The aim of our study is to investigate whether single-nucleotide dystrophin gene (DMD) variants associate with variability in cognitive functions in healthy populations. The study included 1240 participants from the Erasmus Rucphen family (ERF) study and 1464 individuals from the Rotterdam Study (RS). The participants whose exomes were sequenced and who were assessed for various cognitive traits were included in the analysis. To determine the association between DMD variants and cognitive ability, linear (mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In all, the brain dystrophin Dp427 appears to play a role during acquisition of associative learning as well as in general processes involved in memory consolidation. This is in accordance with recent single variant and gene-based analyses showing that dmd-gene variants affecting this full-length brain dystrophin are associated with general variability of cognitive ability in healthy human populations (Vojinovic et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…In all, the brain dystrophin Dp427 appears to play a role during acquisition of associative learning as well as in general processes involved in memory consolidation. This is in accordance with recent single variant and gene-based analyses showing that dmd-gene variants affecting this full-length brain dystrophin are associated with general variability of cognitive ability in healthy human populations (Vojinovic et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…In addition, 3 genes (ABCA7, SLC24A4, SORL1) had a nominally significant interaction with education on memory performance/ decline (p<0.05), and 3 genes (BIN1, CELF1, CR1) were suggestively associated with memory performance/decline (p<0.1) in at least one ethnic group in our study, suggesting that we were able to replicate some of the previous findings implicating Alzheimer's Disease-associated genes in longitudinal assessment of cognitive decline. The final study applied SKAT to exome sequencing data collected from over 2,500 participants in a single gene (DMD) and cognition (Vojinovic, et al, 2015). This gene was not among those that we evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Whether variation in dystrophin expression pattern, affects cognitive domains in phenotypically normal population, has remained an outstanding question. One study reported the role of single nucleotide DMD variants (rs147546024:A > G, an intronic variant; rs1800273:G > A, a missense variant) in cognitively healthy general population 21 . A case study reported manifestation of intellectual disability without usual muscular dystrophy phenotype due to deletion of three base pairs (c.9711_9713del) in the distal region of DMD gene 22 , providing substantial evidence regarding DMD distal region's association with human cognition.…”
mentioning
confidence: 99%